Leaf N resorption efficiency and litter N mineralization rate have a genotypic tradeoff in a silver birch population. Issue 5 (18th April 2018) - Mikola, Juha; Silfver, Tarja; Paaso, Ulla; Possen, Boy J. M. H.; Rousi, Matti
Abstract: Plants enhance N use efficiency by resorbing N from senescing leaves. This can affect litter N mineralization rate due to the C:N‐ratio requirements of microbial growth. We examined genotypic links between leaf N resorption and litter mineralization by collecting leaves and litter from 19 Betula pendula genotypes and following the N release of litter patches on forest ground. We found significant genotypic variation for N resorption efficiency, litter N concentration, cumulative three‐year patch N‐input and litter N release with high broad‐sense heritabilities ( H 2 = 0.28–0.65). The genotype means of N resorption efficiency varied from 46% to 65% and correlated negatively with the genotype means of litter N concentration, cumulative patch N‐input and litter N release. NH4 + yield under patches had a positive genotypic correlation with the cumulative patch N‐input. During the first year of litter decomposition, genotypes varied from N immobilization (max 2.71 mg/g dry litter) to N release (max 1.41 mg/g dry litter), creating a genotypic tradeoff between the N conserved by resorption and the N available for root uptake during the growing season. We speculate that this tradeoff is one likely reason for the remarkably wide genotypic range of N resorption efficiencies in our birch population.